Effects of running-based versus body-weight-based high-intensity interval training on physical fitness in healthy adolescents - Li, Zhen; Liu, Yang; Han, Xiaowei; Zhou, Zhixiong (Frontiers in Physiology, 2023)
Abstract OBJECTIVES: High-intensity interval training improves aerobic endurance, but the effectiveness of different training protocols is unclear. This study compared the effects of running-based high-intensity interval training (R-HIIT) and body weight-based high-intensity interval training (B-HIIT) on physical fitness in adolescents. METHODS: This was a pre-and post-test quasi-experimental design in which a seventh-grade natural class was randomly selected from three homogeneous middle schools, and then the three natural classes were randomly divided into three groups: the R-HIIT group (n = 54), the B-HIIT group (n = 55), and the control group (Con, n = 57). Both intervention groups exercised twice a week for 12 weeks with a 2:1 (1 min:30 s) load-interval ratio and exercise intensity controlled at 70%–85% maximum heart rate. R-HIIT was in the form of running, and B-HIIT was in the form of resistance exercises using the participants’ body weight. The control group was instructed to continue their normal behavior. CRF, muscle strength and endurance, and speed were measured before and after the intervention. Statistical differences between and within groups were determined using repeated measures analysis of variance. RESULTS: Compared to the baseline, both the R-HIIT and B-HIIT intervention groups significantly improved CRF, muscle strength, and speed (p < 0.05). The B-HIIT group was significantly better than R-HIIT in improving CRF (4.48 mL/kg/min vs. 3.34 mL/kg/min, p < 0.05), and only the B-HIIT improved sit-up muscle endurance (ηp2 = 0.30, p < 0.05). CONCLUSIONS: The B-HIIT protocol was significantly more effective than the R-HIIT protocol in developing CRF and improving muscle health indicators. Keywords: HIIT, Middle School Students, VO2max, Muscle Fitness, School Environment